A non-syn-gas catalytic route to methanol production - Wu, CT (2013)
At present, more than 80% of the world’s energy consumption and production of chemicals is originated from the use of fossil resources. There is a tremendous growing interest in utilising biomass molecules for energy provision due to their carbon neutrality. Lower alcohols such as methanol and ethanol if produced from biomass as transportation fuels as well as platform chemicals, can become strategically important for many energy/chemically starved countries. Currently, they are synthesised by indirect and inefficient processes. We show for the first time in this thesis study that ethylene glycol, the simplest representative of biomass-derived polyols, can be directly converted to these two lower alcohols by selective hydrogenolysis over modified Raney Ni and Cu catalysts in hydrogen atmosphere. This work provides essential information that may lead to the development of new catalysts for carbohydrate activation to methanol, a novel but important reaction concerning the important biomass conversion to transportable form of energy. Modification of electronic structure and the adsorption properties of Raney catalysts have therefore been achieved by blending with second metal(s). It is found that the activity and selectivity of this reaction can be significantly affected by this approach. In contrast, there is no subtle effect on methanol selectivity despite a great variation in the d-band centre positions of metal catalysts which show a distinctive effect on other products. Our result suggests that methanol is produced on specific surface sites independent from the other sites at an intrinsic rate and will not be converted to other products by the d-band alteration. On the other hand, it is reported in this thesis that a dramatic improvement in the combined selectivity to methanol/ethanol reaching 80% can be obtained over a Pd/Fe3O4 catalyst under relatively milder conditions (20 bar and 195 oC). This direct production of the non-enzymatic bio-alcohols is established over a carefully prepared co-precipitated Pd/Fe3O4 catalyst which gives a metallic phase of unexpectedly high dispersion ranging from small clusters to individual metal adatoms on defective iron oxide to give the required metal-support interaction for the novel synthesis. It is demonstrated that the small PdFe clusters on iron oxide surface provide the active species responsible for methanol production. In addition, a related Rh/Fe3O4 catalyst synthesised by co-precipitation is also shown to be selective for CO2 and H2 production from a direct methane-oxygen oxidation reaction. As a result, 2.7% conversion of methane with selectivity ratio of CO2/H2 = 4 in a mixed gas feed stream of CH2/O2 = 30 at 300 oC is obtained. The reaction is operated in a kinetically controlled regime at 300oC, where the CO formation from reverse water gas shift reaction is greatly suppressed. It is evident that the Rh/Fe3O4 acts as an interesting bifunctional catalyst for this reaction. This catalyst firstly gives a high dispersion of Rh which is expected to deliver a higher surface energy with enhanced activity. The Rh metal surface provides catalytically active sites for dissociation of methane to adsorbed hydrogen and carbon atoms effectively, and active oxygen on metal surface readily catalyses the carbon atoms to CO. Following these elementary reactions, the surface oxygen from Fe3O4 subsequently converts it to CO2 selectively at the metal-support interface. As a result, the novel study of catalytic biomass conversion and the discoveries of new catalysts are reported in this thesis.